Spatial Distribution of Glycerophospholipids in the Ocular Lens - Pól, Jaroslav; Vidová, Veronika; Hyötyläinen, Tuulia; Volný, Michael; Novák, Petr; Strohalm, Martin; Kostiainen, Risto; Havlíček, Vladimír; Wiedmer, Susanne K.; Holopainen, Juha M. (PLOS ONE, 2011)
Knowledge of the spatial distribution of lipids in the intraocular lens is important for understanding the physiology and biochemistry of this unique tissue and for gaining a better insight into the mechanisms underlying diseases of the lens. Following our previous study showing the spatial distribution of sphingolipids in the porcine lens, the current study used ultra performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC-QTOFMS) to provide the whole lipidome of porcine lens and these studies were supplemented by matrix-assisted laser desorption ionization mass spectrometry imaging (MALDI MSI) of the lens using ultra-high resolution Fourier transform ion cyclotron resonance mass spectrometry (FTICR MS) to determine the spatial distribution of glycerophospholipids. Altogether 172 lipid species were identified with high confidence and their concentration was determined. Sphingomyelins, phosphatidylcholines, and phosphatidylethanolamines were the most abundant lipid classes. We then determined the spatial and concentration-dependent distributions of 20 phosphatidylcholines, 6 phosphatidylethanolamines, and 4 phosphatidic acids. Based on the planar molecular images of the lipids, we report the organization of fiber cell membranes within the ocular lens and suggest roles for these lipids in normal and diseased lenses.